Experimental demonstration of high-order magnetic localized spoof surface plasmons - Gao, Fei (2015)
We experimentally demonstrate that an ultrathin metallic spiral structure is able to support multiple high-order magnetic localized spoof surface plasmons (LSSPs), which were absent in previously reported magnetic LSSPs. Near-field response spectra and near-field mapping are performed in the microwave regime to confirm this phenomenon. We also show that the high-order magnetic LSSPs are more sensitive to the surrounding refractive index change than the previously reported magnetic dipole mode. Our study may be useful in electromagnetic near-field sensing from microwave to infrared frequencies.